Influences of Sn on Properties of Ag-Based and Cu-Based Brazing Filler Metals - Qingcheng Luo (MDPI AG, 2021)
Ag-based and Cu-based brazing filler metals, which are the most widely used brazing materials in industrial manufacturing, have excellent gap-filling properties and can braze almost all the metallic materials and their alloys, except for the low-melting-point metals such as Al and Mg. Therefore, Ag-based and Cu-based brazing filler metals have attracted great attention. In this review, three series of typical Ag-based filler metals: the Ag-Cu, Ag-Cu-Zn, and Ag-Cu-Zn-Sn alloys; and three series of Cu-based filler metals: the crystalline and amorphous Cu-P filler metals, as well as the Cu-Zn filler metals, were chosen as the representatives. The latest research progress on Sn-containing Ag-based and Cu-based brazing filler metals is summarized, and the influences of Sn on the melting characteristics, wettability, microstructure, and mechanical properties of the selected filler metals are analyzed. Based on these, the problems and corresponding solutions in the investigation and application of the Sn-containing Ag-based and Cu-based filler metals are put forward, and the research and development trends of these filler metals are proposed.